The Time-Concentration-Mortality Modeling and Virulence Indices for Strain NGS71814 of Metarhizium anisopliae against the Potato Tuber Moth (PTM), Phthorimaea operculella - Phangthavong, Souksamone; Chen, Bin; Zheng, Yaqiang; Liu, Siyu; Loiheuang, Chanhom; Chanthanouvong, Kita; Chanthakhoun, Vongpasith; Phetlumphun, Bounxian; Vannaphon, Anousith (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Potato tuber moth (PTM), Phthorimaea operculella (Zeller) attack solanaceous crops worldwide. They cause high economic losses. Metarhizium anisopliae is an important entomopathogenic fungi. To determine the effectiveness of this fungus as a biocontrol agent for PTM, virulence of M. anisopliae on 1st, 2nd and 3rd instar larvae, and pupae were conducted, the resulting data were analyzed using a time-dose-mortality modeling technique, yielding the parameters for time and dose effects of the M. anisopliae. The fungi M. anisopliae caused 95%, 100%, 100% and 100% mortality of 1st, 2nd and 3rd instar larvae, and pupae at conidial concentration of 2 × 108 conidia/mL. The estimated parameter (β) for the concentration effect of M. anisopliae was 0.596, 0.66, 0.282 and 1.137 in bioassay 1st, 2nd, 3rd instar larvae, and pupae. Which indicated that the pathogenicity of M. anisopliae against the pupae were greater than that of larvae. Moreover, the t statistics for all parameters estimated were significant (P < 0.01). At 2 × 108 conidia/mL concentration, 3rd and 2nd instar larvae had short lethal times (LT50) of 1.01 and 1.3 d compared with 3.5 and 3.6 d for pupae. The values of LC50 estimated on days 1 to 4 after exposure decreased from 2.27× 108 to 4.64× 101 conidia/mL for the 3rd instar larvae, on days 3 - 10 decreased from 1.51 × 105 to 8.45 × 102 conidia/mL for the 2nd instar larvae, on days 3 - 10 decreased from 1.99 × 106 to 2.43 × 104 conidia/mL for the 1st instar larvae, and on days 1 - 7 decreased for pupae. The estimated of LC90 during the same time period decreasing from 4.07× 1012 to 8.32× 105 conidia/mL. Finally, the LC90 decreasing to 3.21 × 104 conidia/mL until the day 10 for the 3rd instar larvae, decreasing on days 4 - 10 from 2.52× 106 to 5.25× 104 conidia/mL for the 1st and 2nd instar larvae and decreasing to 2.47× 106 conidia/mL on the day 7 for pupae.